Application of BIOME-BGC to simulate Mediterranean forest processes - Chiesi, M.; Maselli, F.; Moriondo, M.; Fibbi, L.; Bindi, M.; Running, S. W. (Ecological Modelling, 2007)
The current work investigates on the applicability of a widespread bio-geochemical model (BIOME-BGC) to estimate seasonal photosynthesis and transpiration within water limited Mediterranean forest environments. The use of the model required a preliminary calibration phase, aimed at setting its ecophysiological parameters to properly simulate the behavior of three Mediterranean species (Quercus ilex L., Quercus cerris L. and Pinus pinaster Ait.). For each of these species, the calibration of BIOME-BGC was performed by adjusting the monthly gross primary productivity (GPP) estimates of 10 forest plots to those of a simpliﬁed parametric model, C-Fix, which is based on the use of satellite and ancillary data. In particular, BIOME-BGC was run modifying the eco-physiological parameters controlling stomatal conductance, in order to identify the best model conﬁgurations to reproduce the spatial, intraand inter-annual GPP variations simulated by C-Fix. Next, the fraction of leaf nitrogen in Rubisco was adjusted to ﬁt also the magnitudes of the C-Fix GPP estimates. The subsequent testing phase consisted of applying the original and calibrated versions of BIOME-BGC in independent forest sites where the three species considered were dominant and for which ﬁeld measurements of photosynthesis and transpiration were available. In all cases the use of the calibrated BIOME-BGC versions led to notably improve the GPP and transpiration estimation accuracy of the original model. The results obtained encourage the operational application of BIOME-BGC in Mediterranean forest environments and indicate a possible strategy to integrate its functions with those of C-Fix.
Keywords: BIOME-BGC; C-Fix; GPP; mediterranean forest; monitoring; Spot-VGT